Harmonic analysis of multiplex rectifier circuits based on diode rectifiers for offshore wind farms - XU Feng; CAO Wenbin; QIAN Zhengxu; HUANG Xiaoming; LIANG Peng; ZHANG Zheren; XU Zheng (Zhejiang dianli)
As the rectification-side devices of the offshore wind power transmission systems， the diode uncontrolled rectification units are a technological hotspot in the offshore wind power sector. Multiplex rectifier circuits are usually employed for diode uncontrolled rectification， with a 12-pulse rectifier circuits being the most common. Theoretical analyses of serial and parallel multiplex wiring in the 12-pulse and the 24-pulse rectifier circuits within the multiplex rectifier circuits have been conducted. This entails studying the harmonic characteristics of the alternating current on the AC side and the voltage on the DC side， deriving the calculation methods for the harmonic numbers and the harmonic amplitudes， and determining the total current harmonic distortion rate and the voltage ripple factor. Comparative analyses are made on the characteristics of 12-pulse and 24-pulse rectifier circuits， investigating the feasibility of applying the 24-pulse rectifier circuits in the diode uncontrolled rectification units. Simulations are carried out on the PSCAD/EMTDC platform.